Dampak Kerja Sama Jepang-Filipina Terhadap Keamanan Maritim Jepang - Sa'pang, Putri Dia Nina; Atika Puspita Marzaman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Japan and the Philippines are countries rich in history, culture, and natural wealth closely tied to the sea. Japan has engaged in maritime diplomacy with the Philippines in the realm of security. Maritime security cooperation between the two nations forms the foundation for collaboration in the management of marine resources, cultural exchanges, economics, and maritime security. The objective of this research is to examine the impacts that can result from Japan-Philippines cooperation on Japan's maritime security. This research employs a mixed-methodology to elucidate the scope and impacts stemming from Japan-Philippines cooperation on Japan's maritime security. The research findings demonstrate that the impact of Japan-Philippines cooperation on maritime security provides critical access and plays a vital role in strengthening regional security in the area. Success in achieving assured maritime security conditions has positive effects on Japan in various sectors, especially in the trade sector. This leads to an increase in trust and facilitates smooth trade activities in the maritime region due to guaranteed maritime security. This approach reflects Japan's commitment to being more proactive in upholding global maritime security and collaborating with its regional partners to achieve shared prosperity and peace in the region and the world.